Assessment of stratigraphic and structural relationships of Devonian-Carboniferous successions in Kanthan area, northern part of the Kinta Valley, Peninsular Malaysia - Ahmad Yahya, Aqilah (2016)
Gunung Kanthan limestone in Chemor, northern part of Kinta Valley, is part the massive Paleozoic Kinta Limestone. The lithostratigraphy of the area was not well assessed due to lack of optimal access; hence many of the studies were carried out in the western Kampar area in tin ex-mines. In this study lithostratigraphic section of Gunung Kanthan limestone succession and the possible structural effects on the lithostratigraphic section were examined. Outcrop description, petrographic study, EDX-SEM, XRD and structural analyses were conducted. The result indicated that the stratigraphy of the Gunung Kanthan might be represented by black shale beds at the bottom of the described section followed by 26 m of crinoidal limestone overlain by 167.6 m of black limestone and 313.5 m of greyish limestone respectively. These lithofacies might be deposited from slope to deeper part of the basin. It was also showed that the section is highly affected by a number of faults striking NS and dipping NE. Therefore, the stratigraphy of the Gunung Kanthan limestone is complicated by the structural deformation in which careful consideration should be taken to establish the stratigraphy of the sedimentary successions in the area.